(3GdQaGgjI GdEbJUGOjI (B:s (3HMK aj GdCSS GdYdejI hGdJWHjbGJ GdYedjI dQaGgjI GdaQO hGdeLJeY (B/s - (3YeQ, MSjfs ((3GdbGgQI(B: s (3OGQ GdacQ GdYQHj(B, s, 1999)
(3JWhjQ fXQjI GdbjeI aj GdEbJUGO GdcdGSjcj(B- (3GdfXQjI GdfeSGhjI aj GdbjeI(B((3fXQjI cGQd efLQ(B)- (3GdfXQjI GdMOjKI aj GdbjeI (B((3fXQjI SJGfdj LbhfR(B)- (3GdTcd GdYGe dOGdI GdefaYI(B- (3fXQjI GdJaVjd GdehVM(B- (3GbJUGOjGJ GdQaGgjI(B- (3TQhW GdGhVGY GdeKdi aj GdEfJGL(B- (3GdfGJL GdGeKd(B- (3SjGSI GdSMQ aj GdefTBJ GdYGeI(B- (3GdEWGQ GdYGe dfJGFL GdQaGgjI aj VhA GdJMdjd GdMOjK(B- (3QaGgjI GdaQO hQaGgjI GdLeGYI hGdeLJeY(B.s
Keywords: (3GdEbJUGOs; (3GdJfejI GdEbJUGOjIs; (3GdQaGgjI GdEbJUGOjIs